Different health effects of indoor‐ and outdoor‐originated PM2.5 on cardiopulmonary function in COPD patients and healthy elderly adults. (1st December 2018) - Chi, Rui; Chen, Chen; Li, Hongyu; Pan, Lu; Zhao, Bin; Deng, Furong; Guo, Xinbiao
Abstract: Numerous research has explored the associations of outdoor or indoor fine particulate matter (PM2.5 ) and health effects; however, few studies compared the effects of indoor PM2.5 originated from outdoor (PM2.5, os ) and indoor sources (PM2.5, is ). To assess the associations of PM2.5, os and PM2.5, is with cardiopulmonary function in patients with chronic obstructive pulmonary disease (COPD) and healthy elderly adults, blood pressure (BP) and pulmonary function were repeatedly examined in 43 COPD patients and their 32 healthy spouses in Beijing, China. Iron was used as tracer element to separate PM2.5, os and PM2.5, is . Mixed‐effects models were applied to assess the associations of PM2.5, os or PM2.5, is and health effects after controlling for potential confounders. There was a reduction in forced expiratory volume in first second (FEV1 ) in COPD patients associated with PM2.5, is during the heating season. PM2.5, os was positively associated with diastolic BP (DBP) in healthy elderly adults during the heating season. There was a reduction in peak expiratory flow (PEF) in healthy elderly adults associated with PM2.5, os during the non‐heating season. Exposure to indoor‐ and outdoor‐originated PM2.5 had different health effects on cardiopulmonary function in different populations. The results provide supporting evidence for improving indoor air quality to promote public health among susceptible population.